Enhanced sensitivity of PTEN-deficient tumors to inhibition of FRAP/mTOR - Neshat, Mehran S. (The National Academy of Sciences, 2001)
Recent evidence places the FRAP/mTOR kinase downstream of the phosphatidyl inositol 3-kinase/Akt-signaling pathway, which is up-regulated in multiple cancers because of loss of the PTEN tumor suppressor gene. We performed biological and biochemical studies to determine whether PTEN-deficient cancer cells are sensitive to pharmacologic inhibition of FRAP/mTOR by using the rapamycin derivative CCI-779. In vitro and in vivo studies of isogenic PTEN(+/+) and PTEN(−/−) mouse cells as well as human cancer cells with defined PTEN status showed that the growth of PTEN null cells was blocked preferentially by pharmacologic FRAP/mTOR inhibition. Enhanced tumor growth caused by constitutive activation of Akt in PTEN(+/+) cells also was reversed by CCI-779 treatment, indicating that FRAP/mTOR functions downstream of Akt in tumorigenesis. Loss of PTEN correlated with increased S6 kinase activity and phosphorylation of ribosomal S6 protein, providing evidence for activation of the FRAP/mTOR pathway in these cells. Differential sensitivity to CCI-779 was not explained by differences in biochemical blockade of the FRAP/mTOR pathway, because S6 phosphorylation was inhibited in sensitive and resistant cell lines. These results provide rationale for testing FRAP/mTOR inhibitors in PTEN null human cancers.